Therapeutic Effect of Stem Cells on Male Infertility in a Rat Model: Histological, Molecular, Biochemical, and Functional Study - Sally S. Mohammed; Mona F. Mansour; Noha A. Salem (Stem Cells International)
Methotrexate (MTX) is a folic acid antagonist, widely used as a chemotherapeutic and immunosuppressive drug, but it is toxic to reproductive systems. In recent years, the era of stem cell applications becomes a promising point as a possible therapeutic agent in male infertility. This study is aimed at evaluating the therapeutic effects of stem cells at histological, molecular, biochemical, and functional levels in a methotrexate-induced testicular damage model. Material and Methods. Thirty rats were divided randomly into three groups (ten rats each): group 1 (control): animals received an intraperitoneal injection of 2 ml phosphate-buffered saline per week for 4 weeks, group 2 (MTX-treated group): animals were intraperitoneally injected with methotrexate (8 mg/kg) once weekly for 4 weeks, and group 3 (ADMSC-treated group): methotrexate-treated animals received a single dose of 1×106 stem cells/rat at the 5th week. At the 8th week, blood samples were collected for hormonal analysis; then, animals were sacrificed. The testes were dissected; the right testis was stained with hematoxylin and eosin. Random sections were taken from group 3 and examined with a fluorescent microscope. The left testis was divided into two specimens: the first was used for an electron microscope and the second was homogenized for molecular and biochemical assessments. Results. Group 2 showed significant histological changes, decreased free testosterone level, decrease in stem cell factor expression, and dysfunction of the oxidation state. The results revealed significant improvement of these parameters. Conclusion. Transplantation of adipose tissue-derived stem cells (ADMSCs) can improve the testicular damage histologically and functionally in a rat model.